An exploratory study of resource selection and evaluation by self-directed leisure learners who participate in online learning communities - Langel, Julia Jeannette (Kansas State University, 2011)
There have been two classic models of the way self-directed learners organize their learning experiences – a planning model, discussed by researchers such as Tough (1971) and Knowles (1975), which considers self-directed learners to be actively and deliberately planning their learning projects, and an environmental model, proposed by Spear and Mocker (1984), which considers these learners to be strongly influenced by what they called the organizing circumstance. Later researchers have found support for both models. Both models posit that learning resources play an important role for self-directed learners, but there hasn’t been much research specifically looking at how learners make resource decisions. For this project, the researcher recruited 13 women from online sewing communities who had reported obtaining a particular hard-to-find sewing resource and interviewed them about their resource decisions and resource libraries. The project asked the questions of how self-directed learners are planning, the criteria they use to choose learning resources, how an environment of plentiful resources and the internet affect these choices, and how learners evaluate their resources. The researcher found that this particular group of learners are conscious only of doing short-term, project-by-project, planning, but reveal another, unconscious level of building mental maps of their entire field of interest, including judgments of their personal interests and evaluations of their personal skill sets. These learners enjoy this learning, and consider their resources to be treats as well as references; they seek relevant content, novelty, and intellectual challenge. They are strongly influenced by their communities, both local and online, but maintain independence in their learning choices.
Keywords: Self-directed learning; Leisure learning; Education, Adult and Continuing (0516)